2019
DOI: 10.1542/hpeds.2018-0104
|View full text |Cite
|
Sign up to set email alerts
|

Newborn Vitamin K Prophylaxis: A Historical Perspective to Understand Modern Barriers to Uptake

Abstract: Since its initial discovery almost a century ago, vitamin K has been labeled as both lifesaving and malignancy causing. This has led to debate of not only its use in general but also regarding its appropriate dose and route. In this article, we review through a historical lens the past 90 years of newborn vitamin K from its discovery through to its modern use of preventing vitamin K deficiency bleeding (VKDB). Although researchers in surveillance studies have shown considerable reductions in VKDB following int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 39 publications
(66 reference statements)
0
9
0
1
Order By: Relevance
“…Although newborn vitamin K 1 prophylaxis is regarded as a safe, reliable and cost-effective intervention against VKDB in many countries including India (2)(3)(4)10,11,17,34,35) , the challenges to implement it continue to exist (36) . Reports from developed countries have increasingly documented instances of parents refusing vitamin K 1 prophylaxis in their newborn children (7,9,33,(37)(38)(39) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although newborn vitamin K 1 prophylaxis is regarded as a safe, reliable and cost-effective intervention against VKDB in many countries including India (2)(3)(4)10,11,17,34,35) , the challenges to implement it continue to exist (36) . Reports from developed countries have increasingly documented instances of parents refusing vitamin K 1 prophylaxis in their newborn children (7,9,33,(37)(38)(39) .…”
Section: Discussionmentioning
confidence: 99%
“…vitamin K 1 predisposes to cancer, etc.) and parental preference for 'alternative' and 'natural' lifestyle (33,(36)(37)(38)(39) . While these are globally relevant issues, a recent online survey brought to light some unique challenges that can hamper vitamin K 1 prophylaxis in lowand middle-income countries, viz., high rates of home deliveries, perception among health workers that neonatal vitamin K prophylaxis is not a priority and supply chain shortcomings (40) .…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for parental decline of vitamin K have been studied worldwide, with very similar results [15][16][17][18][20][21][22][23][24][25][26][27][28]. The principal concerns generally cited are: (1) increased risk of cancer, especially childhood leukemia (not supported by available data);…”
Section: Reasons For Refusal Of Vitamin Kmentioning
confidence: 97%
“…The current overall incidences of lack of neonatal Vitamin K administration and or late VKDB in the United States is unclear. Studies in New Zealand, Australia, Canada and Great Britain suggest incidences of refusal of parental vitamin K administration at birth of 1-7% [9,16,17]. Estimates for the USA range from 0-3.2% of births in hospitals, 14.5% in home births and up to 31% in birthing centers [18].…”
Section: Why a Resurgence Of Late Vkdb?mentioning
confidence: 99%
“…Recent research has revealed multiple barriers to vitamin K adherence, including the debunked theory of cancer association and parental fears of pain and vaccinations, to name a few. 4 Currently, there are no MedEdPORTAL publications on this specific topic. There are several simulation-based publications on topics regarding the ill neonate, including critical congenital heart disease, 5 epilepsy, 6 neonatal resuscitation, 7 febrile infant, 8,9 infant in shock, 10,11 and nonaccidental trauma, 12 as well as one resource addressing newborn medications that includes a discussion of vitamin K. 13 Our simulation case can be seen, therefore, as part of this series on the critically ill neonate in an emergency setting.…”
Section: Introductionmentioning
confidence: 99%